2023
DOI: 10.1088/1475-7516/2023/03/002
|View full text |Cite
|
Sign up to set email alerts
|

Observational constraints on warm natural inflation

Abstract: Warm natural inflation is studied for the case of the original cosine potential. The radiation bath during inflation induces a dissipation (friction) rate in the equation of motion for the inflaton field, which can potentially reduce the field excursion needed for an observationally viable period of inflation. We examine if the dissipation thus provides a mechanism to avoid the large decay constant f ≳ M pl of cold cosine natural inflation. Whereas temperature independent dissipat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…These symmetry properties also suppress radiative and thermal corrections which allow this model and more generally axion-like potentials to be trivially implemented in the context of WI [43,[74][75][76]. This potential in the WI scenario was found to be consistent with observations for super-Planckian and marginal sub-Planckian values for the decay constant f [55,77].…”
Section: Jcap01(2024)032supporting
confidence: 60%
See 2 more Smart Citations
“…These symmetry properties also suppress radiative and thermal corrections which allow this model and more generally axion-like potentials to be trivially implemented in the context of WI [43,[74][75][76]. This potential in the WI scenario was found to be consistent with observations for super-Planckian and marginal sub-Planckian values for the decay constant f [55,77].…”
Section: Jcap01(2024)032supporting
confidence: 60%
“…This module then determines the best fitting function G(Q) via the method of least squares. Specifically, to allow for a direct comparison with previous work, we employ the polynomial fitting functions most prominently used in the literature due to its simplicity [50,55,68,84]:…”
Section: Scalar_dissipation_functionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference is significant in the case of strong dissipation (Q ≫ 1), and particularly for b G ≥ 0, which corresponds to a dissipation rate with a non-negative temperature dependence. For example, if we set Q = 100 and b G = 6.52, which corresponds to the value found for a dissipation rate Υ ∝ T c , with c = 3 [50], we obtain…”
Section: Jcap02(2024)006mentioning
confidence: 71%
“…Recently, a new fit for the function G(Q) was found in[76], also for a cubic dissipation coefficient. We have considered this fit for the βexponential model and found that the difference in the results is minimal, so our conclusions for the model are unchanged.…”
mentioning
confidence: 99%